Ukrainians in Bosnia and Herzegovina from their immigration to the present day - Škiljan, Filip (Historical Thought, 2025)
The author provides information on the immigration of Ukrainians to the territory of Bosnia and Herzegovina in the late 19th and early 20th century. Based on archival sources, the testimonies of informants, collection of newspaper clippings and available literature author writes about the first decades of Ukrainians stay in Bosnia and Herzegovina, about relationship of newcomers to the local Serbs, Croats and Muslims, about organization of the Greek Catholic Church in Bosnia and Herzegovina, about the cultural organization of the Ukrainians in Bosnia and Herzegovina, about the period of the Second World War II and about the emigration of Ukrainians from Bosnia during the Second World War and after the Second World War. Specifically deals about the assimilation of Ukrainian national minority during and immediately after the last war in Bosnia and Herzegovina.